Titanium dioxide in dental enamel as a trace element and its variation with bleaching - Vargas Koudriavtsev, Tatiana (2018)
BACKGROUND: Titanium is a less studied trace element in dental enamel. Literature relates an increased Titanium concentration with a decreased enamel crystal domain size, which in turn is related to a higher color value. The aim of our study was to analyze the effect of tooth bleaching agents on its concentration in dental enamel by means of confocal Raman spectroscopy. MATERIAL AND METHODS: Human teeth were randomly distributed in six experimental groups (n=10) and submitted to different bleaching protocols according to the manufacturer´s instructions. Confocal Raman spectroscopy was carried out in order to identify and quantify the presence of titanium dioxide molecules in enamel prior to and during whitening. Statistical analysis included repeated measures analysis of variance (p≤0.05) and Bonferroni pairwise comparisons. RESULTS: Titanium dioxide concentration was negatively affected by the longer bleaching protocols (at-home bleaching gels). All in-office whitening products increased significantly the studied molecule (p≤0,05). CONCLUSIONS: All dental specimens depicted the presence of titanium dioxide as a trace element in dental enamel. Bleaching gels that have to be applied at higher concentrations but for shorter periods of time increase the concentration of titanium dioxide, whilst at-home whitening gels used for longer periods of time despite the lower concentration caused a loss in titanium.